A systematic review and meta-analysis of randomized controlled trials for the reduction of surgical site infection in closed incision management versus standard of care dressings over closed vascular groin incisions. (June 2020) - Gombert, Alexander; Dillavou, Ellen; D'Agostino, Ralph; Griffin, Leah; Robertson, Julie M; Eells, Mark
Objective: Surgical site infection after groin incision is a common complication and a financial burden to patients and healthcare systems. Closed incision negative pressure therapy (ciNPT) has been associated with decreased surgical site infection rates in published literature. This meta-analysis examines the effect of ciNPT (PREVENA™ Incision Management System; KCI, San Antonio, TX) versus traditional postsurgical dressing use in reducing surgical site infection rates over closed groin incisions following vascular surgery. Methods: A systematic literature search using PubMed, OVID, EMBASE, and QUOSA was performed on 3 January 2019, by two independent researchers and focused on publications between 1 January 2005 and 31 December 2018. The review conformed to the statement and reporting check list of the Preferred Reporting Items for Systematic Reviews and Meta Analyses. Inclusion criteria included abstract or manuscript written in English, published studies, conference abstracts, randomized controlled trials (RCTs), ciNPT usage over closed groin incisions in vascular surgery, comparison of ciNPT use and traditional dressings, study endpoint/outcome of surgical site infection, and study population of >10. Characteristics of study participants, surgical procedure, type of dressing used, duration of treatment, incidence of surgical site infection, and length of follow-up were extracted. Weighted odds ratios and 95% confidence intervals were calculated to pool study and control groups in each publication for analysis. Treatment effects were combined using Mantel-Haenszel risk ratios, and the Chi-Square test was used to assess heterogeneity. Overall, high-risk patients, normal-risk patients, and Szilagyi I, II, III outcomes were assessed between ciNPT and control groups. The Cochrane Collaboration tool was utilized to assess the risk of bias for all studies included in the analysis. Results: A total of 615 articles were identified from the literature search. After removal of excluded studies and duplicates, six RCT studies were available for analysis. In these studies, a total of 362 patients received ciNPT, and 371 patients received traditional dressings (control). Surgical site infection events occurred in 41 ciNPT patients and 107 control patients. The heterogeneity test was nonsignificant ( p  > 0.05). The overall RCT meta-analysis showed a highly significant effect in favor of ciNPT (OR = 3.06, 95% CI [2.05, 4.58], p  < 0.05). High-risk, normal-risk, Szilagyi I, and Szilagyi II meta-analyses were also statistically significant in favor of ciNPT use ( p  < 0.05). The varying RCT inclusion/exclusion criteria, such as differences in procedure types, and patient populations form the major limitations of this study. Conclusions: A statistically significant reduction in the incidence of surgical site infection was seen following ciNPT usage in patients undergoing vascular surgery with groin incisions.